Chronic exposure to polluted urban air aggravates myocardial infarction by impaired cardiac mitochondrial function and dynamics. (15th February 2022) - Marchini, Timoteo; Magnani, Natalia; Garces, Mariana; Kelly, Jazmin; Paz, Mariela; Caceres, Lourdes; Calabro, Valeria; Lasagni Vitar, Romina; Caltana, Laura; Contin, Mario; Reynoso, Sofia; Lago, Nestor; et al.
Abstract: Air pollution exposure positively correlates with increased cardiovascular morbidity and mortality rates, mainly due to myocardial infarction (MI). Herein, we aimed to study the metabolic mechanisms underlying this association, focusing on the evaluation of cardiac mitochondrial function and dynamics, together with its impact over MI progression. An initial time course study was performed in BALB/c mice breathing filtered air (FA) or urban air (UA) in whole-body exposure chambers located in Buenos Aires City downtown for up to 16 weeks (n = 8 per group and time point). After 12 weeks, lung inflammatory cell recruitment was evident in UA-exposed mice. Interestingly, impaired redox metabolism, characterized by decreased lung SOD activity and increased GSSG levels and NOX activity, precede local inflammation in this group. At this selected time point, additional mice were exposed to FA or UA (n = 12 per group) and alveolar macrophage PM uptake and nitric oxide (NO) production was observed in UA-exposed mice, together with increased pro-inflammatory cytokine levels (TNF-α and IL-6) in BAL and plasma. Consequently, impaired heart tissue oxygen metabolism and altered mitochondrial ultrastructure and function were observed in UA-exposed mice after 12 weeks, characterized by decreased active state respiration and ATP production rates, and enhanced mitochondrial H2 O2 production. Moreover, disturbed cardiac mitochondrial dynamics was detected in this group. This scenario led to a significant increase in the area of infarcted tissue following myocardial ischemia reperfusion injury in vivo, from 43 ± 3% of the area at risk in mice breathing FA to 66 ± 4% in UA-exposed mice (n = 6 per group, p < 0.01), together with a sustained increase in LVEDP during myocardial reperfusion. Taken together, our data unravel cardiac mitochondrial mechanisms that contribute to the understanding of the adverse health effects of urban air pollution exposure, and ultimately highlight the importance of considering environmental factors in the development of cardiovascular diseases. Graphical abstract: Image 1 Highlights: A chronic exposure to urban air impairs lung redox metabolism and immunity. Alveolar macrophages readily uptake air pollution particulate matter. Exposure to urban air alters cardiac mitochondrial ultrastructure and function. Mitochondrial dynamics is blunted in the heart of mice exposed to urban air. A chronic exposure to urban air aggravates myocardial ischemia reperfusion injury.